2015
DOI: 10.1128/jvi.02492-14
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hepatitis C Virus Infection Impairs Ribavirin Antiviral Activity through Clathrin-Mediated Trafficking of Equilibrative Nucleoside Transporter 1

Abstract: Ribavirin (RBV) continues to be an important component of interferon-free hepatitis C treatment regimens, as RBV alone does not inhibit hepatitis C virus (HCV) replication effectively; the reason for this ineffectiveness has not been established. In this study, we investigated the RBV resistance mechanism using a persistently HCV-infected cell culture system. The antiviral activity of RBV against HCV was progressively impaired in the persistently infected culture, whereas interferon lambda 1 (IFN-1), a type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Therefore, we speculate that any exogenous agent that induces ER-stress and autophagy response additively inhibits the expression of IFNAR1, leading to impairment of IFN-α treatment response against HCV. Chronic ER-stress and autophagy response also affect RBV antiviral activity by downregulating membrane expression of ENT1 [ 41 ]. Our results provide a mechanism for how FFA-treated HCV cell culture impairs the antiviral response of IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that any exogenous agent that induces ER-stress and autophagy response additively inhibits the expression of IFNAR1, leading to impairment of IFN-α treatment response against HCV. Chronic ER-stress and autophagy response also affect RBV antiviral activity by downregulating membrane expression of ENT1 [ 41 ]. Our results provide a mechanism for how FFA-treated HCV cell culture impairs the antiviral response of IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, many investigators, including our own, showed that HCV‐associated ER stress induced an autophagy response, which results in impaired host innate immunity through blocking endogenous IFN production7, 9 and also escapes from exogenously added IFN‐α and ribavirin (RBV)‐based antiviral therapy through degradation of interferon‐alpha receptor 1 and RBV transporter 10, 11. In this report, we found that HCV infection induces chaperone‐mediated autophagy (CMA) as a cell survival mechanism to avoid the ER‐stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased level of p62 was observed in CHC contrary to AIH, suggestive of an autophagic function occurring at a much higher rate. This is supported by the observation that the level of p62 decreased within 3-6 days following HCV infection in Huh7.5 cells due to an increase in the autophagy response, which was indicated by an elevated level of LC3 [34].…”
Section: Discussionmentioning
confidence: 58%